Rompendo os Tapumes: uma Proposta de interação vivenciada através da restauração na comunidade de São Sebastião das Águas Claras/MG - Moema Nascimento Queiroz (2003)
This paper reports on the work carried out during the revitalization of the Capela de São Sebastião (St. Sebastian Chapel) and deals with three aspects: the promotion of a restoration through a private initiative and the managerial difficulties ensuing from the limitations on dialogue and interaction between teams that is still experienced; the understanding of the influences the surroundig environment exerts on the process of degradation, as well as the role played by the building in its community, São Sebastião das Águas Claras (macacos) - Nova Lima/MG. This project led to a multi-disciplinary proposal aimed at bestowing a significant level of quality to the preservation of all heritage by educational means, through the interaction amongst the preservationist, the restorer and the local community, utilizing the concept of preventative conservation as an additional tool for the awakening of a critical mind, aware both of the need to preserve historical heritage and of the relationship it bears with personal and cultural identity. In this manner, it can be demonstrated that cultural heritage education can also be achieved outside museums and cultural centers, through the promotion of the possibility of a new stance regarding cultural and historical heritage and the establishment of its links with the values given to it by the community, leaving them with the challenge of undertajing and continuing the activities developed therein.